(3WHbGJ GdMaGX GdTGaYjjfs - (3QVhGf Hf eMqeO Hf jhSa GdoYrbHj GdTGaYqj GdeUQj, CHh GdfYje,J (B852 (3g` s
(3ChdgG (B:s
(3hHYO, agPG efJbi ef WHbGJ GdESfhj QMeg Gddg EfJbjJ ajg ef XaQJ Hg ef GdMaGX GdTGaYjjf s
(3BNQgG (B:s
(3Je GdefJbi ef WHbGJ GdabgGA bGd oefJbjg QVhGf Hf eMeO GHf jhSa(B: (3aQZJ efg VMhI jhe GdSHJ GdoeHGQc KGdK YTQjf ef TgQ QLH SfI SJ hYTQjf hKeGfeGFI s
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B27 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B166s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B270 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs